2010
DOI: 10.1186/1745-6215-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Bojungikgitang and banhabaekchulchonmatang in adult patients with tinnitus, a randomized, double-blind, three-arm, placebo-controlled trial - study protocol

Abstract: BackgroundTinnitus is the perception of hearing a sound for which there is no external acoustic source. It is often associated with sudden, temporary hearing loss and has a clear impact on a patient's quality of life. Despite numerous trials, there are no treatments that can be considered well established in terms of providing replicable long-term tinnitus reduction. Complementary and alternative medical approaches have been employed to relieve symptoms of tinnitus. Bojungikgitang and banhabaekchulchonmatang a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…The complex mechanism and innate diversity in etiology of tinnitus have made its treatment a dilemma for physicians and specially otolaryngologists. Despite considerable number of researches, none of the so far presented medications and treatments has resulted in a sustained reduction in perception of tinnitus [16]. No appropriately controlled clinical trials have been successful to prove efficacy of a single drug.…”
Section: Current Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex mechanism and innate diversity in etiology of tinnitus have made its treatment a dilemma for physicians and specially otolaryngologists. Despite considerable number of researches, none of the so far presented medications and treatments has resulted in a sustained reduction in perception of tinnitus [16]. No appropriately controlled clinical trials have been successful to prove efficacy of a single drug.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Bojungikgitang and banhabaekchulchonmatang have been approved by Korea Food and Drug Administration and are being widely used in Korea for treatment of Tinnitus because of their very low rate of adverse effects [16]. These two herbal medications have found their places among Korean people and physicians.…”
Section: Bojungikgitang and Banhabaekchulchonmatang (Traditional Korementioning
confidence: 99%
See 1 more Smart Citation
“…Experiments modeling acoustic trauma induced hearing loss in guinea pigs showed that RA improves auditory function by inhibiting ROS and nitric oxide in cochlear cells. (Kim et al, 2010) Received for publication on 21 st April 2018. Accepted for publication on 27 th June 2018…”
Section: Radix Astragalimentioning
confidence: 99%
“…Eine Studie mit ähnlichem Design, allerdings mit drei Behandlungsarmen, befasste sich mit der Behandlung von Tinnitus durch zwei koreanische Pflanzenpräparate -Ergebnisse wurden allerdings nicht prä-sentiert [18]. Besser sah es aus mit einer Untersuchung [27] der auch im Innenohr durchblutungsfördernd wirkenden Isolate Aescin und Troxerutin.…”
Section: Ausgewählte Klinische Studienunclassified